Family functioning, social skills and suicidal ideation in fifth-year high school students from emblematic educational institutions Francisco Antonio de Zela and Francisco Bolognesi de Tacna, in 2011 - Torres Ojeda, Enrique Hugo (2013)
Objective: Determine the relationship between family functioning and social skills with suicidal ideation in the students of the fifth year of secondary school. Attended by 250 students of the I.E.E. Francisco Bolognesi and 270 students of the I.E.E. Francisco A. de Zela. Method: We used a design non-experimental, crosssectional, descriptive and correlational. For the production and recording data, test was applied to family functioning, the scale of social skills and the test of suicidal ideation of Beck. Results: The results determined that the 11% of females and 12.5 % of the students have ever thought about suicide. Also that there is a 29 percent of students who live on the inside of a functional family, that the 44.8 % living with a family moderately family and 26.1 % live with a dysfunctional family and severely dysfunctional. With regard to social skills was found that the skills of planning recorded a higher percentage of students in the optimal levels and very optimal (77.2 %). In contrast, the social skills with a lower percentage in optimal levels and very best were those related to the feelings (61.3 %). Conclusion: It was found that the family functioning as social skills is significantly related with suicidal ideation in the pupils of the 5th year of secondary educational institutions Francisco Antonio de Zela and Francisco Bolognesi of Tacna